Comparison of crystalloid and colloid co-load combined with norepinephrine prophylaxis on post-spinal anesthesia hypotension during cesarean delivery: a randomized sequential allocation dose-finding study - Chen, Yi; Xu, Xiangzhao; Qin, Rui; Guo, Lei; Ni, Xinli (Frontiers in Medicine, 2023)
Background Fluid loading is an essential component of treatment for reducing the incidence of post-spinal anesthesia hypotension and is necessary to maintain intravascular volume, perfuse tissues, and control spinal anesthesia hypotension after sympathetic blockade. We performed a randomized sequential allocation dose-finding study to compare the effects of 10 mL/kg crystalloid and 6% hydroxyethyl starch (130/0.4) co-load on the ED90 of prophylactic norepinephrine infusion for preventing post-spinal anesthesia hypotension during cesarean delivery. Methods Eighty patients were randomly allocated to receive either a 10 mL/kg crystalloid (Crystalloid Group, n = 40) or 6% hydroxyethyl starch (130/0.4) (Colloid Group, n = 40) co-load combined with prophylactic norepinephrine infusion during spinal anesthesia for cesarean delivery. The first patient received an initial prophylactic norepinephrine infusion rate of 0.025 μg/kg/min. Subsequent patients received a 0.005 μg/kg/min gradient dose of prophylactic norepinephrine. This dose was administered as a gradient based on its effectiveness for preventing post-spinal anesthesia hypotension (defined as SBP < 80% of baseline value) and determined by the up-and-down sequential allocation methodology. The primary study outcome was the ED90 of prophylactic norepinephrine infusion. Secondary outcomes included the incidence of post-spinal anesthesia hypotension, bradycardia, hypertension, Apgar scores, and umbilical artery blood gas values were also measured. Results The ED90 values of prophylactic norepinephrine infusion for preventing post-spinal anesthesia hypotension during cesarean delivery were 0.063 μg (95% CI: 0.050 to 0.064) and 0.062 μg (95% CI: 0.045 to 0.064) using isotonic regression analysis, and 0.068 μg (95% CI: 0.056 to 0.353) and 0.060 μg (95% CI: 0.050 to 3.590) using probit regression analysis in the Crystalloid Group and Colloid Group, respectively. The secondary outcomes were comparable between the two groups. Conclusion The administration of a 10 mL/kg 6% hydroxyethyl starch (130/0.4) does not provide additional benefits compared to crystalloid co-load in reducing the ED90 of prophylactic norepinephrine infusion for preventing post-spinal anesthesia hypotension during cesarean delivery.